Second Corinthians - Stegman, Thomas (Catholic commentary on sacred scripture, 2009)
Introduction -- Outline of 2 Corinthians -- Setting the stage (1:1/11) -- Aligned with the "yes" of Jesus (1:12/22) -- Clearing the air (1:23/2:13) -- Minister of the new covenant (2:14/3:11) -- Transformed into "the image of God" (3:12/4:6) -- Suffering as a mark of apostleship (4:7/15) -- Resurrection hope (4:16/5:10) -- Christ's compelling love andGod's gift of reconciliation (5:11/21) -- Resume of the minister of reconciliation (6:1/10) -- "Open your hearts" (6:11/7:4) -- Looking back, once more (7:5/16) -- Collection for the Jerusalem church (1) : participating in the work of grace (8:1/24) -- Collection for the Jerusalem church (2) : theological foundation and fruits (9:1/15) -- "Battling" on behalf of God (10:1/18) -- Paul vs. the "superapostles" (11:1/15) -- Foolish boasting (11:16/33) -- Power in weakness (12:1/13) -- Announcing His third visit (12:14/13:4) -- "Take on the character of Jesus" (13:5/13)